This I Believe - Long, Sylvester (Tufts Archival Research Center, 2006)
Sylvester Long recounts his experiences growing up in an Ohio farming family, and describes his belief that he is merely a "window" through which to reveal God's light to others and God's "subcontractor" whose work is done ultimately for and with God.